Gamma delta+ intraepithelial lymphocytes and coeliac lymphogram in a diagnostic approach to coeliac disease in patients with seronegative villous atrophy. Issue 7 (12th February 2020) - Fernández‐Bañares, Fernando; Crespo, Laura; Núñez, Concepción; López‐Palacios, Natalia; Tristán, Eva; Vivas, Santiago; Farrais, Sergio; Arau, Beatriz; Vidal, Judith; Roy, Garbiñe; Esteve, Maria
Summary: Background: The causes of seronegative villous atrophy can be grouped as coeliac or noncoeliac related. There is no consensus on how to approach subjects with seronegative coeliac disease. Aim: To evaluate the accuracy of both an increase in CD3 + T‐cell receptor gamma delta + (TCRγδ + ) intraepithelial lymphocytes and coeliac lymphogram for the diagnosis of coeliac disease in patients with seronegative villous atrophy. Methods: Sixty‐seven consecutive patients with seronegative villous atrophy were included. Duodenal biopsies to assess TCRγδ + and CD3 − by flow cytometry were performed at the index endoscopy. Coeliac lymphogram was defined as an increase in TCRγδ + plus a decrease in CD3 − intraepithelial lymphocytes. Sensitivity, specificity and Fagan's nomogram were calculated. Results: Coeliac disease was diagnosed in 37 patients and noncoeliac villous atrophy in 30. Coeliac patients were younger (39 ± 3 vs 55 ± 3 years; P = 0.001), more often showed HLA‐DQ2/8 (97.6% vs 61%; P = 0.002) and had a more severe histology (61% vs 32% Marsh 3b‐c; P = 0.055), as compared to noncoeliac ones. Coeliac lymphogram was associated with a sensitivity of 87% (CI, 73.7‐95) and specificity of 96.7% (82.7‐99.9), whereas evaluating only TCRγδ + yielded a sensitivity of 91.3% (79.2‐97.6) and specificity of 83.3% (65.3‐94.3). Among patients with a pre‐test coeliac disease probability of 30%, post‐test probabilities were 92% and 5% for positive and negative coeliac lymphogram, and 70% and 4% for positive and negative TCRγδ + . Conclusions: Coeliac lymphogram was associated with a high level of diagnostic evidence either against or in favour of coeliac disease in patients with seronegative villous atrophy.